2012
DOI: 10.1371/journal.pone.0049723
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human T Cells Secrete Exosomes That Participate in IL-2 Mediated Immune Response Signaling

Abstract: It has previously been shown that nano-meter sized vesicles (30–100 nm), exosomes, secreted by antigen presenting cells can induce T cell responses thus showing the potential of exosomes to be used as immunological tools. Additionally, activated CD3+ T cells can secrete exosomes that have the ability to modulate different immunological responses. Here, we investigated what effects exosomes originating from activated CD3+ T cells have on resting CD3+ T cells by studying T cell proliferation, cytokine production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 41 publications
(51 reference statements)
4
106
0
Order By: Relevance
“…A similar pattern of regulation was observed by Wahlgren et al [19] who looked at the combined effects of IL-2 and autologous exosomes on the cytokine profile of T lymphocytes. Conspicuously, we found that the genes repressed by treatment with EVs in this study outnumbered the genes enhanced by EV treatment.…”
Section: Experimental Validation Of the Microarray Resultssupporting
confidence: 79%
“…A similar pattern of regulation was observed by Wahlgren et al [19] who looked at the combined effects of IL-2 and autologous exosomes on the cytokine profile of T lymphocytes. Conspicuously, we found that the genes repressed by treatment with EVs in this study outnumbered the genes enhanced by EV treatment.…”
Section: Experimental Validation Of the Microarray Resultssupporting
confidence: 79%
“…Nanovesicles called exosomes play important roles in intercellular communication, cellular inflammation, antigen presentation, programmed cell death, and pathogenesis (25)(26)(27)(28)(29). Recently, much interest has developed in mechanisms of extracellular delivery of nucleic acids and proteins among virally infected and uninfected bystander cells, and exosomes have been shown to play an important role in viral pathogenesis and control of host immune responses to infection (28, 30 -32).…”
mentioning
confidence: 99%
“…An exosome is a microcapsule membranous structure secreted from living cells and its functions vary depending on the cell source (10)(11)(12). Previous studies have primarily focused on exosomes derived from tumor cells and DCs.…”
Section: Discussionmentioning
confidence: 99%